Sociodemographic and Obstetric Determinants of Antenatal Depression in Jimma Medical Center, Southwest Ethiopia: Facility Based Case–Control Study - Alenko A; Dejene S; Girma S (Dove Medical Press, 2020)
Arefayne Alenko,1 Sisay Dejene,2 Shimelis Girma1 1Department of Psychiatry, Faculty of Medical Science, Institute of Health, Jimma University, Jimma, Ethiopia; 2Department of Health Service Management, College of Medicine and Health Sciences, Hawassa University, Hawassa, EthiopiaCorrespondence: Arefayne AlenkoDepartment of Psychiatry, Faculty of Medical Science, Institute of Health, Jimma University, PO Box 378, Jimma, EthiopiaTel +251967670149Email arefeaynealenko@gmail.comBackground: Worldwide, 10– 20% of women experience depression during pregnancy. In sub-Saharan countries, depression during pregnancy is estimated to be 15– 57%. Even though there is a high burden of depression during pregnancy, little attention has been given to identify sociodemographic and obstetric determinants in diverse populations like Ethiopia.Objective: To identify sociodemographic and obstetric determinants of antenatal depression among women attending an antenatal clinic at Jimma Medical Center, southwest Ethiopia.Patients and Methods: A case–control study was conducted among 246 pregnant mothers (82 cases and 164 controls) attending an antenatal clinic in Jimma Medical Center from June 1 to August 30, 2019. Antenatal depression was assessed using the Beck Depression Inventory-II. Epidata 3.1 and SPSS v24 were used for data entry and analysis, respectively. Adjusted odds ratios (AOR) and 95%CIs were estimated using logistic regression models. Statistical significance was set at P< 0.05.Results: Married mothers were 67% (AOR=0.33, 95%CI: 0.15– 0.75), housewives were 97% (AOR=0.03, 95%CI: 0.01– 0.14), private workers were 87% (AOR=0.13, 95%CI: 0.04– 0.44), and government employees were 84% (AOR=0.16, 95%CI: 0.05– 0.46), less likely to develop antenatal depression. Multigravida were 88% (AOR=0.12, 95%CI: 0.04– 0.37) less likely to develop antenatal depression. Third trimester pregnancy was four times (AOR=4.04, 95%CI: 1.51– 10.81) more likely to have depression. Mothers who having wanted pregnancy were 83% (AOR=0.17, 95%CI: 0.04– 0.81) less likely to develop antenatal depression compared with mothers having unwanted pregnancy.Conclusion and Recommendation: Being married, multigravida, having wanted pregnancy and occupation status (housewives, private workers and government employees) can protect mothers from developing antenatal depression. Mothers with third trimester pregnancy were four times more likely to have depression. Designing a screening and intervention strategy for antenatal depression must consider the aforementioned protective and risk factors.Keywords: antenatal depression, determinants, Ethiopia